Literature Reviews: The Role and Participation of Local Communities in Various Countries to Increasing Disaster Awareness - Yasaroh, Sabila; Wilujeng, Insih; Hestiana, Hestiana (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Disaster awareness as part of the Sustainable Development Goals needs to be increased in the last few decades. Various methods are used in disaster risk reduction and management, one of which is by involving the participation of local communities because it turns out that disaster education in schools is not enough without real application in the community. The purpose of this literature review is to describe an intervention involving local communities in various countries as the main tool in raising disaster awareness. Search for various reference databases, such as research journals, journal reviews, and data published in 2015-2020. The keywords used in the search for articles were role, participation, local community, state, disaster awareness, disaster risk reduction, disaster risk management, disaster education, preparedness, mitigation, earthquakes, volcanic eruptions, floods, forest fires by obtaining 10 articles appropriate through the analysis of objectives, suitability of topics, research methods used, sample size, the results of each article, and the limitations that occur. There have been effective results in increasing disaster awareness by involving local communities consisting of various elements such as civil society communities, school communities, children, and university students.